Dramaturgy and its role in the theatrical show industry - BOUGHOUAS, Zoubida (Journal of Human Sciences, 2020)
The theatrical discourse has its specificity, because it is based on the text and the spectacle, it can only be realized by moving the text on the stage, and it must therefore have another writing that takes into account this transition, and it is the work sought by the Playwright, mediator between the theatrical text and the show, from there begins its centralization, the centralization that we seek in this article through the definition of the term dramaturgy and its origins in western theatrical culture and its articulations with the functions of the author and director, then look for the extent of the activation of this function in the Arab theatrical act.